Implementation of the nursing process in Sub-Saharan Africa: An integrative review of literature - Grace Tadzong-Awasum; Adelphine Dufashwenayesu (Elsevier, 2021)
Background: The nursing process is a necessary guide to understanding the scientific basis and essence of nursing practice. It requires some degree of critical thinking from nurses to ensure improved collaboration, continuity of care and better health outcomes. The objective of this literature review was to identify the issues related to implementation of the nursing process in sub-Saharan African countries. Methodology: The reviewed studies were selected from a series of original studies carried out in sub-Saharan African countries. Literature on implementation of the nursing process was sought from PubMed, CINAHL, MEDLINE, African Index Medicus data bases, and Google Scholar. Findings: Twenty-six articles fitted the inclusion criteria and were retained. The findings reveal an enormous gap in the literature for nursing process implementation. After data analysis, three themes were identified, namely: (1) inadequate knowledge of the nursing process; (2) stressful working conditions; and (3) low staff levels (understaffing). These three issues negatively influence implementation of the nursing process in most sub-Saharan African hospitals. Conclusion and recommendations: Although the nursing process is an essential tool in improving patient and health outcomes, it is not adequately implemented in almost all hospitals in Sub-Saharan Africa. It is recommended that nurses, midwives and nursing leaders find ways of improving the acquisition of professional knowledge on the nursing process and advocate for improved working conditions.